Pengaruh Pandemic Covid-19 Terhadap Minat Pengambilan KUR UMKM Pada Industri Perbankan di Kota Jayapura - Soumokil, Markus Setiawan; Syauta, Jack Henry (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The Covid-19 pandemic causes economic activity to decline and affects the level of economic income of the community, business actors and banks. This study aims to determine the effect of the Covid-19 Pandemic on the interest in taking KUR UMKM in the Banking Industry in the city of Jayapura. This research uses qualitative and quantitative approaches conducted over 5 (five) months. Data collection using observation, interviews, online questionnaires (google form) and literature studies with descriptive descriptive statistical analysis tools. The results showed that the provision of people's business credit is very supportive and has a significant positive effect on the development of micro, small and medium enterprises in Jayapura City, which is expected to be able to develop MSMEs in Jayapura to be even better in the future.